Communication technology use in post-divorce coparenting relationships: A typology and associations with post-divorce adjustment. (December 2021) - Russell, Luke T; Ferraro, Anthony J; Beckmeyer, Jonathon J; Markham, Melinda S; Wilkins-Clark, Renée E; Zimmermann, McKenzie L
Divorced parents are increasingly expected to carry out shared physical custody of minor children by maintaining ongoing communication with their ex-spouse. Digital and cellular technologies have created new mediums for divorced parents to carry out communication (e.g., texting, email, and social media). In this study, we identified a typology of divorced parents' use of five communication mediums with their former spouse using latent class analysis. We also examined how parent, post-divorce relationship, and family characteristics were associated with class membership. The four classes we identified were multi-method communicators who extensively used all communication mediums; phone-facilitated communicators who had moderate usage of face-to-face communication, with higher frequency of talking on the phone or texting; text and email communicators who used minimal synchronous communication, relying on texting or emailing; and limited communication texters who had low use of all communication mediums, but when they did communicate, did so via text. Divorced coparents have widely incorporated communication technologies into their post-divorce coparenting relationships. Understanding how new communication technologies are associated with individual, relational, and family adjustment to divorce can help inform research, policy, and practice.